PERTANGGUNG JAWABAN BPJS KETENAGAKERJAAN TERHADAP PENYELENGGARAAN JAMINAN SOSIAL BAGI PESERTA EKS JAMSOSTEK - Muhammad Febriansyah Putra; Budiman Ginting; Hasim Purba; Utary Maharany Barus (USU LAW JOURNAL, 2015)
ABSTRACT Social Security Law and the Law BPJS give meaning of the word "transformation" as a change in the form of BUMN Persero which organizes social security programs, a BPJS. Changes in body shape significantly change the characteristics of social security as an adjustment to change the philosophy of the organization of the social security program. Changes characteristic means a change of the legal entity that includes the establishment, scope of work and authority of the body which in turn is followed by changes in the organizational structure, working procedures and organizational culture. BUMN Persero social security consists of PT. (Persero) Askes, PT. (Persero) ASABRI, PT. (Persero) Jamsostek, PT. (Persero) TASPEN. Privaat fourth is a legal entity established pursuant to Law No. 19 of 2003 on SOE governance and subject to the provisions stipulated in Law No. 40 Year 2007 regarding Limited Liability Company. SOE transformation Persero be BPJS aims to fulfill the mandate of the funding principle and the principle of non-profit SJSN, where the funds collected by BPJS is a trust fund managed by BPJS participants to provide maximum benefit for the participants. Key Words : Accountability BPJS Employment; Implementation of Social Insurance; Former Participants of Jamsostek.